Association Between Fatigue and Basic Life Support Readiness Among Indonesian Red Cross Volunteers in Prehospital Emergency Care: A Cross-Sectional Study - Sri Anik Rustini, Sri Anik x; Salsabila, Nurul Kholida; Sustrami, Dys; Widyastuti, Merina; Kristiningrum, Sifira (Journal of Applied Nursing and Health, 2026)
Background: Fatigue is a common challenge among humanitarian volunteers involved in pre-hospital emergency response and can reduce their readiness to perform Basic Life Support (BLS). However, evidence on the relationship between fatigue and BLS readiness among Indonesian Red Cross (PMI) volunteers is limited. This study aimed to analyze the relationship between fatigue levels and readiness to perform Basic Life Support among PMI volunteers in Surabaya, Indonesia. Methods: This quantitative analytical study used a cross-sectional design and was conducted in accordance with the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines. A total of 110 Indonesian Red Cross (PMI) volunteers were recruited using total sampling. Fatigue was measured using the Subjective Self-Rating Test (SSRT), while BLS readiness was assessed using a validated and reliable 10-item questionnaire (validity coefficient ≥ 0.50; Cronbach's α = 0.845). Data were analyzed using the Shapiro–Wilk normality test and Spearman's rank correlation with a significance level of 0.05. Results: Among the 110 PMI volunteers, the majority were female (70.9%), aged 17–25 years (98.2%), and had completed high school (73.6%). Most volunteers experienced high fatigue (64.5%), while the largest proportion was categorized as almost ready to perform Basic Life Support (39.1%). Crosstabulation showed a decreasing trend in BLS readiness as fatigue levels increased. Spearman's rank correlation revealed a strong and statistically significant negative correlation between fatigue levels and BLS readiness (rₛ = −0.630, p < 0.001), indicating a large effect size. Conclusion: Fatigue is a significant factor influencing emergency preparedness and readiness to perform Basic Life Support among Indonesian Red Cross (PMI) volunteers. These findings support the integration of fatigue management into volunteer preparedness and emergency response programs to strengthen prehospital care capacity. Future longitudinal and multivariable studies are recommended further to investigate causal relationships and additional determinants of volunteer preparedness.